Therapeutic methods in the treatment of triple-negative breast cancer - a review - Karolina Joanna Ziętara; Mateusz Pawlina; Karolina Widłak; Aleksandra Orzechowska; Karolina Raksa; Katarzyna Nowakowska; Martyna Lewkowicz; Karol Chromiak (Kazimierz Wielki University, 2022)
Breast cancer is a common female malignancy characterized by the presence of multiple subtypes taking into account, among other things, hormonal activity. The purpose of this study is to show the therapeutic options for triple-negative breast cancer (TNBC). A review of the literature in databases such as PubMed, Google Scholar, and Web of Science by keywords was performed, taking into account papers from 2017-2022. The main therapeutic approaches are surgical intervention and systemic chemotherapy (neoadjuvant and adjuvant). Unsatisfactory results from chemotherapy have prompted researchers to work on other methods to combat TNBC. Clinical trials are being conducted on the use of immunotherapy focusing mainly on molecules against PD-1, PD-L1, and CTLA-4. Targeted therapy is the latest proposed form of therapy, which offers the possibility of introducing a drug in the future that will be tailored to the patient's needs limiting the negative therapeutic impact.